PSIKOLOGI DALAM TRADISI ILMIAH ISLAM - Norhidayat, Norhidayat (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2013)
This paper described about psychology which had been discussing in the traditions ofIslamic thought. Either in religious perpective, Sufis or philosophys, the psychology inthe traditions of Islamic thought was basically different from the psychology in thetradition of western-secular thought. However the last psychology was reduced as astudy of mind and behavior or mental processes, the other has been a study of soul asimmaterial substansions, it was neither of body nor part of body, it would be existwhenever the body had been died and each may be repaid what it had earned.